MENCIPTAKAN MILENIAL ENTREPRENEUR MELALUI PEMBELAJARAN KEWIRAUSAHAAN SOSIAL PADA MAHASISWA - Nazlah Rachma Panggabean; Dearma Sariani Sinaga (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
Several problems are found in the field of students 'low understanding of social entrepreneurship, lack of students' skills in social entrepreneurship and low motivation to become entrepreneurial. This research was conducted at Darma Agung University which is engaged in education where the vision of Darma Agung University is to become a leading and character-based university entrepreneurship in 2035, therefore it must be supported by students' understanding of entrepreneurship learning with social entrepreneurship specifications. The goal is to create young entrepreneurs through social entrepreneurship courses among students. With the growth of entrepreneurs among students, it means not only growing the economy but also aiming at increasing the ability of local communities to utilize the resources owned by Indonesia in general, and the areas where they live in particular. Apart from being capable young entrepreneurs, of course this nation also needs entrepreneurs who have empathy or have social skills. Entrepreneurs can also move in the social field. In addition to being a young generation who is financially successful, the nation's young generation is also expected to have social concern for the surrounding environment. This study using path analysis method (path analysis) is a method to determine the effect of each variable to be studied. In this study there are 2 independent variables, namely interest and ability, then the dependent variable is social entrepreneurship learning and the intermediate variable is the millineal entrepreneur. From the results of data processing the effect of interest, the ability to learn social entrepreneurship is 74.4% while the remaining 25.6% is influenced by other factors that are not researched. Meanwhile, the influence of interest, ability and social entrepreneurship learning on millineal entrepreneur is 23.3%, while the remaining 76.7% is influenced by other factors that are not examined.